PERSONALITY EDUCATION ACCORDING TO ALLAMA MUHAMMAD IQBAL - Imam Bahroni (At-Ta'dib, 2015)
This paper is aimed at discussing the concept of Personality Education according to Allama Muhammad Iqbal. In relation with the concept, Muhammad Iqbal (1873-1938), emphasized the proper development of the individuality of man. He maintained that an individual should be exposed to all kinds of formative and challenging experiences; otherwise his individuality will shrink and wither[1]. Iqbal underscored the importance of freedom, which allowed for experimentation with the environment, for the exercise of choice and discrimination in the use of methods and substance, and for learning by direct, firsthand experience. Despite his emphasis on the individual, Iqbal did not ignore the role of the community and its culture in the give-and-take dynamics with the individual. Iqbal also subscribed to the view that there must be harmony between the material and spiritual elements in man, which educational theory should consider. He valued intellect, but he criticized contemporary thought for overstressing it at the expense of intuition or love. From Iqbal's writings, the characteristics of the good man could be inferred. First, the good man is creative and original, for creativity is the most precious and distinctive gift of man. He must be able to use his intelligence to harness the forces of nature for his own good and also to increase his knowledge and power. Secondly, the good man lives his life in the name of the Lord, dedicating his powers and knowledge to working out His purpose and thereby deserving himself for the position of God's vicegerent on earth.[1] K.G. Saiyidain, (1977), Iqbal's educational philosophy, 8th ed.,Lahore: SH Muhammad Ashraf, p. 14.